The impact of reflective practice on teacher candidates' attitudes towards individuals with disabilities and professional identity. Issue 6 (2nd November 2021) - Szocik, Katherine; Gerry, Margaret A.; Nagro, Sarah A.
ABSTRACT: With the global rise of inclusive educational practices, it is important to understand teacher candidates' perceptions of disability and inclusion. The purpose of this one group experimental research design study is to examine the impact of a graduate-level course on perceptions of individuals with disabilities and professional identity. Eighty-three teacher candidates in the United States enrolled in a graduate-level introduction to special education course completed a series of reflections about disability and inclusion. Researchers found that perceived reflective ability significantly predicted teacher candidates' perceptions towards individuals with disabilities. Regardless of general or special education career paths, teacher candidates significantly changed the way they perceived individuals with disabilities. Specifically, at the end of the semester, teacher candidates viewed individuals with disabilities as more different than individuals without disabilities. Implications surrounding the importance of reflective practice in domestic and international teacher education practice and research will be addressed.